Radioimmunotherapy for Brain Metastases: The Potential for Inflammation as a Target of Choice - Corroyer-Dulmont, Aurélien; Jaudet, Cyril; Frelin, Anne-Marie; Fantin, Jade; Weyts, Kathleen; Vallis, Katherine A.; Falzone, Nadia; Sibson, Nicola R.; Chérel, Michel; Kraeber-Bodéré, Françoise; Batalla, Alain; Bardet, Stéphane; et al. (Frontiers in Oncology, 2021)
Brain metastases (BM) are frequently detected during follow-up of patients with malignant tumors, particularly in those with advanced disease. Despite major progress in systemic anti-cancer treatments, average overall survival of these patients remains limited (6 months from diagnosis). Also, cognitive decline is regularly reported especially in patients treated with whole brain external beam radiotherapy (WBRT), due to absorbed radiation dose in healthy brain tissue. New targeted therapies, for an earlier and/or more specific treatment of the tumor and its microenvironment, are needed. Radioimmunotherapy (RIT), combination of a radionuclide to a specific antibody, appears to be a promising tool. Inflammation, which is involved in multiple steps, including the early phase, of BM development, is attractive as a relevant target for RIT. This review will focus on (1) early biomarkers of inflammation in BM pertinent for RIT, (2) state of the art studies on RIT for BM, and (3) the importance of dosimetry to RIT in BM. These two last points will be addressed in comparison to conventional EBRT treatment, particularly with respect to the balance between tumor control and healthy tissue complications. Finally, because new diagnostic imaging techniques show potential for the detection of BM at an early stage of the disease, we focus particularly on this therapeutic window.